2018
DOI: 10.1177/0300060518796759
|View full text |Cite
|
Sign up to set email alerts
|

Optimized beagle model for maxillary sinus floor augmentation via a mini-lateral window with simultaneous implant placement

Abstract: ObjectiveThis study was performed to establish an optimized beagle model for maxillary sinus floor augmentation via a mini-lateral window with simultaneous implant placement.MethodsTwelve beagles underwent maxillary sinus floor augmentation via a mini-lateral window with simultaneous implant placement through sites selected by analyzing preoperative cone beam computed tomography (CBCT) images. During the experiment, no maxillary teeth were extracted and the infraorbital nerve was not severed. The osteotomy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In the consistence of what assumed by Zhu and colleagues, 20 the authors believe that the high RFA values of the small antrostomy group after 6 months, as detected by the readings of the Osstell device, attributes to the size reduction of the side window as well as its coverage with the collagen membrane, which minimized the fibrous invasion and maximized the blood supply and the osteogenic potential of the underlying constitute.…”
Section: Discussionmentioning
confidence: 54%
“…In the consistence of what assumed by Zhu and colleagues, 20 the authors believe that the high RFA values of the small antrostomy group after 6 months, as detected by the readings of the Osstell device, attributes to the size reduction of the side window as well as its coverage with the collagen membrane, which minimized the fibrous invasion and maximized the blood supply and the osteogenic potential of the underlying constitute.…”
Section: Discussionmentioning
confidence: 54%
“…We have introduced a modified beagle model for maxillary sinus floor augmentation via a 5mm‐diameter mini‐lateral window with simultaneous implant placement in 2018 (Zhu et al., 2018). This model is established on the maxillary recess of dog, which is only seemed as a sinus equivalent due to the absence of the Schneiderian membrane and pneumatization (Wetzel et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the remaining 152, 37 fulfilled the inclusion and exclusion criteria and were used for data extraction. 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Twelve 20 , 21 , 25 , 31 , 34 , 36 , 37 , 39 , 40 , 42 , 50 , 52 out of the 37 included studies clearly reported the administration of pre‐ or peri‐operative corticosteroids. None of the included articles specifically compared lateral MSA procedure outcomes with or without the use of corticosteroids.…”
Section: Resultsmentioning
confidence: 99%